On such a full sea - Lee, Chang-rae (Riverhead Books, a member of Penguin Group (USA), 2014)
"From the beloved award-winning author of Native Speaker and The Surrendered, a highly provocative, deeply affecting story of one woman's legendary quest in a shocking, future America. On Such a Full Sea takes Chang-rae Lee's elegance of prose, his masterly storytelling, and his long-standing interests in identity, culture, work, and love, and lifts them to a new plane. Stepping from the realistic and historical territories of his previous work, Lee brings us into a world created from scratch. Against a vividly imagined future America, Lee tells a stunning, surprising, and riveting story that will change the way readers think about the world they live in. In a future, long-declining America, society is strictly stratified by class. Long-abandoned urban neighborhoods have been repurposed as highwalled, self-contained labor colonies. And the members of the labor class-descendants of those brought over en masse many years earlier from environmentally ruined provincial China-find purpose and identity in their work to provide pristine produce and fish to the small, elite, satellite charter villages that ring the labor settlement. In this world lives Fan, a female fish-tank diver, who leaves her home in the B-Mor settlement (once known as Baltimore), when the man she loves mysteriously disappears. Fan's journey to find him takes her out of the safety of B-Mor, through the anarchic Open Counties, where crime is rampant with scant governmental oversight, and to a faraway charter village, in a quest that will soon become legend to those she left behind"--